Business Strategy based on the comparison of Sun Tzu and Khandaq War Management Strategy - Ifan Fardian; Afif Zaerofi; Zulkarnain Muhammad Ali (Al Tijarah, 2022)
Among the business strategy models that have developed so far, some use military strategy as a business strategy model. Business strategy has many similarities to military strategy, and one of them is Sun Tzu's war strategy. In the history of Islam, there is a war strategy of the Prophet SAW whose principle is similar to Sun Tzu's war strategy, this strategy is the Khandaq war strategy. It is necessary to research to compare the principles of Sun Tzu's war strategy and the Khandaq War. This research aims to; 1). Discover the principles of Sun Tzu's war strategy and Khandaq's war strategy, 2). Compares the two principles of Sun Tzu's war strategy and Khandaq's war strategy and 3). Formulating the principles of business strategy as a result of the comparison of the principles of Sun Tzu's war strategy and Khandaq's war strategy. The research uses a qualitative approach and to analyze the data, the Analytic Network Processing (ANP) method is used. The data was obtained through interviews with 18 selected respondents, consisting of 9 sharia economics academics and 9 sharia business practitioners.This study found; 1). Khandaq war and Sun Tzu war, have the same 6 main strategic principles (goal formulation, condition calculation, strategy determination, strategy implementation, control strategy, and leadership) and can be used in business strategy, 2). Interesting findings from this study are that there are differences in the forming indicators and 3). The results of the preparation of ANP compose the principles of business strategy as a result of the comparison of the strategies of Sun Tzu and Khandaq, namely the principles of leadership, then the formulation of objectives, implementation strategies, control strategies, determination of strategies and calculation of conditions with all forming indicators. So that the priority principles of the ANP processed strategy can be used as the principles of a new business strategy.